2013
DOI: 10.1021/ja312572v
|View full text |Cite
|
Sign up to set email alerts
|

EcdGHK Are Three Tailoring Iron Oxygenases for Amino Acid Building Blocks of the Echinocandin Scaffold

Abstract: The echinocandins are a small group of fungal N-acylated cyclic hexapeptides that are fungicidal for candida strains and fungistatic for aspergilli by targeting cell wall 1,3-β-glucan synthases. The side chains of all six amino acid building blocks have hydroxyl groups, including the nonproteinogenic 4R,5R-dihydroxy-Orn1, 4R-OH-Pro3, 3S, 4S-dihydroxy-homoTyr4 and 3S-OH-4S-Me-Pro6. The echinocandin (ecd) gene cluster contains two predicted nonheme mononuclear iron oxygenase genes (ecdG,K) and one encoding a P45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
113
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(124 citation statements)
references
References 28 publications
6
113
0
4
Order By: Relevance
“…After oxidative decarboxylation, an α-keto acid is obtained, which is finally transaminated to provide homotyrosine. In a subsequent 2013 study, Tang, Walsh, and colleagues revealed the activity of the three oxygenases in the Ecd section of Ecd/Hty, which will be discussed in the next section [16].…”
Section: Resistancesmentioning
confidence: 96%
See 4 more Smart Citations
“…After oxidative decarboxylation, an α-keto acid is obtained, which is finally transaminated to provide homotyrosine. In a subsequent 2013 study, Tang, Walsh, and colleagues revealed the activity of the three oxygenases in the Ecd section of Ecd/Hty, which will be discussed in the next section [16].…”
Section: Resistancesmentioning
confidence: 96%
“…Figure 3) [16]. Nevertheless, the order of biosynthetic steps, especially of the oxidations catalyzed by up to six dioxygenases, remains enigmatic.…”
Section: Oxidation Reactions In Echinocandin Biosynthesismentioning
confidence: 99%
See 3 more Smart Citations